Knowing Puberty With E-Modules - Ketut Yuli Ayu Wulandari; I Made Tegeh; Ndara Tanggu Renda (Indonesian Journal Of Educational Research and Review, 2021)
Teachers still do not use media/teaching materials when teaching, especially in online learning. So that teachers still do not use innovative media/teaching materials in learning. Therefore, this study aims to develop an e-module in science learning on Puberty as seen from its validity. This type of research refers to the ADDIE development model procedure that consists of the stages of analysis, design, development, implementation, and evaluation. In this study, the implementation and evaluation stages were not carried out because they are currently still in the Covid-19 pandemic period, so they must comply with health protocols. The subjects in this study were e-modules on science learning on Puberty and experts who were competent in their fields. This study used a questionnaire method in collecting data. A rating scale instrument was used in an assessment sheet for two material experts, two media experts, and two practitioners to determine e-module validity. The test results of the science e-module on the topic of Puberty were calculated and converted into a five-scale guideline table. Based on the developed e-module, the science e-module validity test results from material experts, media experts, and practitioners obtained very good qualifications and were declared valid. So that the science e-module on the topic of Puberty is suitable for use by teachers when teaching because this e-module has an attractive appearance and the content/content in the e-module is complete so that it can support student learning activities.